A Systematic Review on Cake Application for Students’ Learning Motivation and Vocabulary Mastery: English - Sang Ayu Made Diah Utami Putri; Ni Made Ratminingsih; Made Hery Santosa (Journal of English Development, 2023)
Indonesian secondary school students need help in gaining new languages. Indonesian students find learning English as a new language is difficult due to the need for English vocabulary. By looking at that problem, the Indonesian Ministry of Education emphasizes integrating technology into the learning process. The integration of technology, especially mobile applications, suits with K-13 and Merdeka curriculum. In this way, teenagers like implementing new technology in their learning process. The integration of the Cake application is one of the mobile applications to implement in language classrooms due to its benefits. Therefore, this study is a systematic literature review to find the integration of MALL, especially the Cake Application, in improving students' learning motivation and vocabulary mastery. Around 19 out of 74 studies were selected by using the PRISMA model to support this study. The results show that Cake Application can facilitate students in gaining new vocabulary and increasing their learning motivation. Therefore, the Cake application is the new suggestion for teachers to access students' vocabulary needs.